MEMBANGUN SISTEM KEAMANAN ARP SPOOFING MEMANFAATKAN ARPWATCH DAN ADDONS FIREFOX - Zonggonau, Kristopedus; Sajati, Haruno (Compiler, 2015)
The Development of information Technology, especially computer networks and the service in a rejuvenate the human side. The development of the internet is very widespread. The security level digital data becomes vulnerable to attack by the attacker. Arp spoofing is one of the attacks in a network that can be used to view digital data traffic such as emails, passwords and etc, when is running in the network. The process of prevention againtst arp spoofing attacks, made an application to detect and block the attacker in the network by Firefox Addons. Attacker will be directly blocking (drop) into to Mikrotik OS. Users avoid the attack arp spoofing. The results of testing one, two and three can be detect and block the presentation of the results of 83%, so That’s the terms of security in the network can be safe from attack to the attacker.